Pontic-Caucasian influences in Southern Pannonia and the Eastern Hallstatt Culture - Potrebica, Hrvoje (Array, 2002)
In the Late Bronze Age, southern Pannonia and the southeastern Alpine region were the area of the Urnfield Culture, while in the Early Iron Age it was the area of the Eastern Hallstatt Culture. The main feature that could be connected with the eastern influences is the Hallstatt warrior concept that was created in the process of transition from a rather leveled social frame of the Urnfield Culture to the highly stratified and hierarchical society of the Early Iron Age. Although a clearly defined warrior aristocracy dominated Hallstatt society, it is very hard to identify the so-called “ Thraco-Cimmerian” presence that allegedly triggered that transition. However, it is obvious that an outside factor strongly influenced the local population and transformed their social structure introducing a strong horsemen element that eventually developed in warrior aristocracy.